Sustaining irrigated agriculture for food security: a perspective from Pakistan - Qureshi, Asad Sarwar; Fatima, Aamira (2012)
Humanity is facing an enormous challenge in managing water to secure adequate food production. By the middle of this century, the world?s population is projected to reach 9.1 billion, 34 percent higher than today. Nearly all of this increase will occur in developing countries. In order to respond to the expected demand of this larger, more urban and, on average, richer population, food production must increase by about 70% as estimated by the FAO. It is an enormous task because the required increase in food production to meet future needs will have to be achieved with fewer land and water resources. Food insecurity in Pakistan is a product of poverty and inadequate food availability. During the past two decades, 1987-2007, food poverty incidence in the country shows that about one-third of the households were living below the food poverty line and they were not meeting their nutritional requirements. The incidence of food poverty is higher in rural areas (35%), than in urban areas (26%). In Pakistan, irrigated agriculture is vital for future food security because it produces more than 90% of the total grain production. With the decreasing amounts of available water, the challenge of sustaining irrigated agriculture is increasing by the day. This paper reviews the situation in Pakistan and suggests pathways to sustain irrigated agriculture in order to meet future food requirements.